Elucidating the molecular mechanism that determines the specific localisation of gurken mRNA during Drosophila development - Gill, K (2017)
mRNA localisation is a widely used mechanism for achieving temporal-spatial restriction of protein expression and is essential during development to establish cell polarity. mRNA localisation is particularly well studied in the Drosophila egg chamber where gurken mRNA is localised to the dorsal-anterior corner of the oocyte in a Dynein-dependent process that establishes the anterior-posterior and dorsal-ventral axes of the future embryo. An RNA stem-loop called the gurken localisation signal is necessary and sufficient to drive gurken localisation through interactions with a specific complement of protein factors. However, the exact RNA sequence and structural features required to promote each stage of gurken localisation are unknown. Using a live-cell injection assay I have dissected regions of the mRNA signal that are responsible for driving gurken transport and anchoring through their association with Egalitarian, Me31B and Squid proteins. I show the structure of an AU-rich stem and a purine stack are essential for gurken transport, and demonstrate that the size of the internal loop between these stems is important. These features of the localisation signal are essential for recruitment of Egalitarian, which links the mRNA to the Dynein transport machinery. I also show that these mRNA sequence and structural elements are present in several other Dynein-transported mRNAs. The bulge at the distal end of the gurken localisation signal is important for anchoring grk at the dorsal-anterior of the oocyte, possibly through Squid binding, and the proximal third of the signal is essential for recruitment of the translation component Me31B. These studies indicate that the role of the gurken localisation signal in controlling gurken transport, anchoring and translation can be mapped to distinct regions of the signal and provide insights into how the signal carries out these numerous functions at a molecular level. Determining the molecular interactions involved in mRNA localisation improves our understanding of how specificity is generated to direct different mRNAs to distinct regions of the cell to restrict protein expression.